Empowering Senior Cochlear Implant Users at Home via a Tablet Computer Application - Philips, Birgit; Smits, Cas; Govaerts, Paul J.; Doorn, Inge; Vanpoucke, Filiep (American journal of audiology, 2018)
The introduction of connectivity technologies in hearing implants allows new ways to support cochlear implant (CI) users remotely. Some functionalities and services that are traditionally only available in an in-clinic care model can now also be accessed at home. This study explores the feasibility of a prototype of a tablet computer application (MyHearingApp [MHA]) in a group of senior experienced CI users at home, evaluating usability and user motivation. Based on user feedback, a tablet computer application (MHA) for the Cochlear Nucleus 6 CP910 sound processor was designed implementing six different functionalities: (a) My Hearing Tests, (b) My Environment, (c) My Hearing Journey, (d) Tip of the Day, (e) Recipient Portal, and (f) Program Use and Events. The clinical evaluation design was a prospective study of the MHA in 16 senior experienced CI users. During 4 weeks, participants could freely explore the functionalities. At the end, the usability and their motivation for uptake and adherence were measured using a baseline and follow-up questionnaire. Based on the System Usability Score (as part of the follow-up questionnaire), a good level of usability was indicated (M = 75.6, range: 62.5-92.5, SD = 8.6). The ability to perform hearing tests at home is ranked as the most relevant functionality within the MHA. According to the Intrinsic Motivation Inventory (Deci, Eghrari, Patrick, & Leone, 1994) questionnaire (as part of the follow-up questionnaire), participants reported high levels of interest and enjoyment, found themselves competent, and did not experience pressure while working with the app. This study evaluated a tablet computer application (MHA) for experienced senior CI users by means of a prospective design, which provided novel insights into delivering CI care into the home of the CI user. The user feedback from this small-scale study suggests that the participants are open to take more responsibility for and to become a more active actor in their own hearing care, if only this is facilitated with the right tools. This may foster the evolution from a clinic-led to a more patient-centered care model, where CI users feel more empowered in the self-management of their hearing implant device.